2019
DOI: 10.1097/nna.0000000000000705
|View full text |Cite
|
Sign up to set email alerts
|

Asking for Feedback

Abstract: OBJECTIVE The purpose of this study was to understand clinical nurses’ perceptions of their participation in a formal, annual peer review process at a metropolitan community hospital. BACKGROUND Peer review is an essential component of professional nursing practice for self-regulation of the practice and promotion of quality and safety. Robust empirical evidence of formalized and effective peer review nursing processes is not evident. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…31 Some participants found being evaluated by a team with “ fresh eye” encouraged them to explore alternative approaches to existing issues, 30 and some participants would like to expand the scope of the peer review process. 26 Conversely, a few participants expressed their displeasure when feedback ventured into clinical territories. 29 It is important that the scope of the peer review process is mutually agreed before the review and is adhered to during the process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Some participants found being evaluated by a team with “ fresh eye” encouraged them to explore alternative approaches to existing issues, 30 and some participants would like to expand the scope of the peer review process. 26 Conversely, a few participants expressed their displeasure when feedback ventured into clinical territories. 29 It is important that the scope of the peer review process is mutually agreed before the review and is adhered to during the process.…”
Section: Resultsmentioning
confidence: 99%
“…One study indicated that although it was defined as “… among RN, ” participants were still unclear about who should be involved in the process. 8 Some defined peers as working in similar roles and settings 9 or someone with the same rank 26 while Davys et al 32 just simply stated “ two colleagues …” One study did not explicitly define peers in the article but intimated that peers could be the participants' “ senior ,” supervisor, or line manager in the same profession. 33…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bowen-Brady et al 6 noted in their research that peer feedback promoted the practice of accountability and autonomy, which improves patient outcomes. Although research supports this, there is lack of evidence to support a standardized process for meaningful peer feedback.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Bowen-Brady et al 6 noted in their study that nurses voiced concern regarding annual peer review being held against them and felt that they might receive repercussions, including monetary, because of it. Nurses were also concerned that they did not believe they had the skills to engage their peers in difficult conversations regarding performance 6 . Gentry 8 protected the anonymity of the peer evaluator from the nurse being evaluated to allow peers to share honest feedback without retribution during annual peer reviews.…”
Section: Review Of Literaturementioning
confidence: 99%